Comparison of out-of-plane short axis with in-plane long axis for ultrasound-guided radial arterial cannulation: A systematic review with trial sequential analysis of randomised controlled trials - Sun, Xia-xuan; Lv, Meng; Du, Wen-ya; Liu, Yi; Zhang, Haixia; Wang, Yue-lan (Frontiers in Cardiovascular Medicine, 2022)
Background: It is controversial whether the short-axis out-of-plane or long-axis in-plane approach is a better needling technique for ultrasound-guidance radial artery cannulation. We aimed to compare the efficacy and safety of the two approaches for ultrasound-guided radial artery cannulation. Methods: A systematic search of Medline, Embase, the Cochrane Library, and Web of Science for relevant articles published until 1 May 2021 was conducted. Randomised controlled trials comparing the long-axis in-plane and short-axis out-of-plane approaches were included. Review Manager software version 5.4, STATA version 14.2, and TSA version 0.9.5.10 Beta were used for statistical analysis. Risk of bias and methodological quality of all studies included in this review were assessed according to the Cochrane Collaboration tool for the risk of bias. Subgroup analyses and meta-regression were performed to explore sources of heterogeneity. Results: The rate of cannula insertion success on the first attempt was similar between the short-axis out-of-plane and long-axis in-plane approaches (RR=1.03; 95% CI:0.83 to 1.28; P=0.79; I2=83.0%). No significant differences were observed in total time to successful cannulation between the two approaches (MD=-3.9; 95% CI:-18.30 to 10.49; P=0.6; I²=97%). However, the required information size for the success rate of the first attempt and total time to successful cannulation was not reached. Conclusion: It remains inconclusive whether short-axis out-of-plane is a better choice for radial arterial cannulation than the long-axis in-plane approach. Inexperienced operators may need more attempts and longer ultrasound location time with the short-axis out-of-plane technique. Systemic review registration: CRD42021236098, International prospective register of systematic reviews (PROSPERO).